Distal femur fractures have a higher mortality rate compared to hip fractures among the elderly: Insights from the National Trauma Data Bank. Issue 7 (July 2021) - Tsai, Sung Huang Laurent; Lin, Tung-Yi; Tischler, Eric H.; Hung, Kuo-Hsien; Chen, Chien-Hao; Osgood, Greg Michael; Fu, Tsai-Sheng; Su, Chun-Yi
Highlights: Distal femur fractures have increased risk for in-patient mortality compared with hip fractures. Distal femur fractures have longer length of stay and required ventilation use compared to hip fractures. Secondary fracture patterns vary among patients with distal femur and hip fractures. Abstract: Introduction: The comparison of mortality and morbidity between distal femur (DF) and hip fracture in the old age is rarely reported in the literature. We aim to analyze a nationwide database among the elderly to compare the outcomes between hip fractures and distal femur fractures in the United States. Materials and Methods: A retrospective analysis of the National Trauma Data Bank was queried between 2007-2014 to identify distal femur (DF) and hip fracture patients greater than 65 years of age. Outcomes analyzed included in-hospital mortality, total hospital length of stay(LOS), intensive care unit length of stay(ICU-LOS), length of ventilation use and hospital discharge disposition. Multivariable regression models were performed to adjust for potential confounders. Statistical significance was established at p < 0.001. Results: 26, 325 (10.1%) and 233, 213 (89.9%) patients reported a diagnosis of DF and hip fracture, respectively. The inpatient mortality rate was significantly higher in the distal femur fracture group (8.3% vs. 6.7%), with significantly longer LOS (7.87 vs. 6.65), ICU-LOS (1.50 vs. 0.73), and required ventilation days (0.74 vs. 0.27). Multivariable analyses demonstrated that hip fracture patients had a lower mortality (adjusted odds ratio [aOR], 0.80; 95% CI [0.76, -0.85]; p < 0.001), shorter LOS ([aOR], -0.31; 95% CI [-0.39, -0.23]; P < 0.001), and more likely to be discharged home ([aOR], 0.88; 95% CI, 0.85, 0.91; P < 0.001, compared to DF fracture patients. Conclusion: After adjusting for potential factors, DF fracture patients have a significantly higher mortality, longer LOS, and less likely to be discharged home compared to hip fractures among the elderly. These results may suggest clinicians and caregivers for closely monitoring of clinical conditions for these patients. Level of Evidence: III.